Microbial Enzymatic Synthesis of Amikacin Analogs With Antibacterial Activity Against Multidrug-Resistant Pathogens - Ban, Yeon Hee; Song, Myoung Chong; Jeong, Joong Ho; Kwun, Min Seok; Kim, Chang Rae; Ryu, Hwi So; Kim, Eunji; Park, Je Won; Lee, Dong Gun; Yoon, Yeo Joon (Frontiers in Microbiology, 2021)
With the constant emergence of multidrug-resistant gram-negative bacteria, interest in the development of new aminoglycoside (AG) antibiotics for clinical use has increased. The regioselective modification of AG scaffolds could be an efficient approach for the development of new antibiotics with improved therapeutic potency. We enzymatically synthesized three amikacin analogs containing structural modifications in the amino groups and evaluated their antibacterial activity and cytotoxicity. Among them, 6′-N-acyl-3″-N-methylated analogs showed improved antibacterial activity against the multidrug-resistant gram-negative bacteria tested, while exhibiting reduced in vitro nephrotoxicity compared to amikacin. This study demonstrated that the modifications of the 6′-amino group as well as the 3″-amino group have noteworthy advantages for circumventing the AG-resistance mechanism. The regiospecific enzymatic modification could be exploited to develop novel antibacterial agents with improved pharmacological potential.